New solitary wave solutions to the coupled Maccari's system - Vahidi, Javad; Zekavatmand, Sayyed Masood; Rezazadeh, Hadi; İnç, Mustafa; Akinlar, Mehmet Ali; Chu, Yu-Ming (Elsevier, 2021)
The aim of this study is to find new exact solutions to the coupled Maccaris system by extended rational sinecosine and rational sinh-cosh methods. By means of these methods, we found some fresh solitons of the above mentioned equation. The solutions are expressed in the form of new periodic,dark,bright and bright periodic solitons solutions. These methods are efficient, powerful, and they can be used as an alternative to establish new soliton of different types of differential PDEs applied in mathematical physics. Also, in order to visualize the underlying dynamics of the obtained soliton solutions, 2D and 3D plots are drawn. Computational results indicate not only the efficiency and strength of the methods but also further possible applicability potential of these techniques to some other significant nonlinear PDEs.
Keywords: Coupled Maccari's system; Soliton solutions with complex structure; Sine-cosine and sinh-cosh techniques